Development and evaluation of 0.5 mm isotropic resolution T1‐weighted and DTI templates of the older adult brain: Neuroimaging / Normal brain aging. (7th December 2020) - Niaz, Mohammad Rakeen; Ridwan, Abdur Raquib; Wu, Yingjuan; Qi, Xiaoxiao; Zhang, Shengwei; Bennett, David A; Arfanakis, Konstantinos
Abstract: Background: Human brain MRI templates with low spatial resolution lack important fine details due to partial volume effects. The purpose of this work was to introduce a novel approach for high‐resolution template construction based on principles of super‐resolution, and using this technique, to develop high‐resolution T1‐weighted and DTI templates of the older adult brain. Method: T1‐weighted (222 images, 1mm isotropic) and DTI (202 images, 2mm isotropic) brain MRI data from non‐demented older adults (65‐95 age‐range, male:female=1:1) participating in the Memory and Aging Project were used in this work (Fig.1). The raw images were spatially normalized in a 0.5mm isotropic resolution space using conventional template building methods. The resulting non‐linear deformations were utilized to map the signals from raw space to exact physical locations in the 0.5mm template space, minimizing interpolations that occur in conventional template‐building method. The final signal in a 0.5mm isotropic voxel in template space was calculated as the weighted average of all signals included in that voxel using a Gaussian kernel. The new T1‐weighted template, MIITRA_0.5mm_T1, was compared to MCALT_0.5mm, ICBM2009b_0.5mm, Colin27_0.5mm, and MIITRA_1mm_T1 (Fig.2A). The new DTI template, MIITRA_0.5mm_DTI, was compared to ICBM81, NTU, IIT_v5.0, EVE, and IXI (Fig.4A). The templates were evaluated in terms of image quality and spatial normalization accuracy achieved when used as references for alignment of MRI data from a large number of older adults. Result: Fine structures were resolved in MIITRA_0.5mm_T1 in contrast to MCALT_0.5mm and MIITRA_1mm_T1 (Fig.2B). Visual inspection revealed atypical brain features in the cortex of MCALT_0.5mm (red circles). MIITRA_0.5mm_T1 has higher image sharpness (Fig.3A) and allowed higher inter‐subject spatial normalization accuracy of older adult T1‐weighted data (Fig.3B, C, D) compared to other templates. Fine white matter structures such as the anterior commissure, posterior commissure, inter‐thalamic adhesion and optic chiasm were clearly resolved in MIITRA_0.5mm_DTI (Fig.4B), in contrast to other DTI templates. MIITRA_0.5mm_DTI exhibits higher image sharpness (Fig.5A) and allowed higher inter‐subject spatial normalization accuracy of older adult DTI data (Fig.5B, C, D, E, F) compared to other templates. Conclusion: MIITRA_0.5mm_T1 and MIITRA_0.5mm_DTI are high‐quality, high‐resolution templates of the older adult brain and allow higher spatial normalization accuracy of older adult data compared to other available templates.